Growth and lipid class composition of the Arctic pelagic amphipod Themisto libellula - Noyon, Margaux; Narcy, Fanny; Gasparini, S.; Mayzaud, P. (Marine Biology, 2011)
Carnivorous zooplankton is a key element to the energy transfer through the arctic food web, linking lipid rich herbivores to the top predators. We investigated the growth and lipid dynamic of the Arctic pelagic amphipod Themisto libellula in Kongsfjorden (Svalbard, 79°N) from May to October 2007. Additional samplings were performed in spring and summer 2006 and further north in Rijpfjorden (80°N), in September 2006 and 2007. In Kongsfjorden, the first free-swimming stages (3 mm) appeared early May and reached their adult length (25 mm), in October. During their first year, they grew according to a Von Bertalanffy model and most probably constituted a single cohort. Juveniles had the highest growth rate (0.19 mm day−1) and revealed relatively low total lipid (TL) content (about 2.5% wet weight (WW)) with phospholipids as the major lipid class. Sub-adults showed a distinct decrease of growth rates which coincided with the increase of neutral lipid storage, reflecting a switch in energy allocation, from somatic growth to lipid storage. Indeed wax esters (WE) increased up to 48.5% TL on average in adults in 2006 while triacylglycerols (TAG) remained almost constant below 25.2% TL. The absence of lipid accumulation (in disproportion of the weight) in 2007 could be explained by a higher metabolism of T. libellula or preys of lower quality. In Rijpfjorden, adults in their second year continued accumulating lipid (up to 10% WW) with high and similar proportions of both lipid classes, WE and TAG. We highlighted that T. libellula exhibited a variable lipid metabolism along its life cycle depending on its physiological needs and environmental conditions.